Beyond green practices: A systematic review of mechanisms and boundary conditions shaping sustainable performance in the Chinese context - Tian, Yuxin; Chaemchoy, Sukanya; Siribanpitak, Pruet (Edelweiss Applied Science and Technology, 2026)
Organizations increasingly adopt green organizational practices, yet previous studies offer limited explanations for when and how these practices translate into sustainable performance, particularly in the Chinese context. Addressing this gap, this study conducts a PRISMA-guided systematic literature review of 336 peer-reviewed empirical studies drawn from Web of Science, Scopus, and CNKI. Through thematic synthesis, the review consolidates fragmented evidence into an integrated framework. The findings reveal that existing studies are primarily grounded in four theoretical perspectives: resource-based, institutional, leadership, and relational. Meanwhile, the green practices influence sustainable performance through two interdependent pathways: a capability pathway centered on green innovation and organizational capabilities, and a cultural-psychological pathway centered on organizational culture, identity, and employee states. Evidence further indicates that sustainable leadership functions as a critical boundary condition by shaping strategic attention, resource allocation, and implementation consistency, thereby explaining performance variation across firms. The study concludes that green practices create performance potential but require leadership activation and employee enactment to generate sustained outcomes. Practically, the findings suggest that organizations should prioritize leadership-driven, culturally embedded sustainability strategies rather than relying solely on technical or compliance-based initiatives.